Early detection of chemotherapy-induced cardiotoxicity in breast cancer patients: a comprehensive analysis using speckle tracking echocardiography - Zhang, Ning; Wang, Na; Zhang, Yanyan; Liu, Ya; Pei, Miaomiao; Liu, Gaiqin; Jia, Xinle; Guo, Xuejia (Frontiers in Cardiovascular Medicine, 2024)
Chemotherapy-induced cardiotoxicity poses a significant challenge in the treatment of breast cancer, potentially compromising both the efficacy of cancer therapy and cardiac health of patients. This study aimed to enhance the early detection of cardiotoxic effects by integrating advanced imaging modalities and biomarker analysis, thereby facilitating timely interventions to mitigate cardiac risk. A prospective cohort design was employed, enrolling breast cancer patients scheduled for potentially cardiotoxic chemotherapy regimens. The study utilized a comprehensive diagnostic toolkit, including echocardiography with strain imaging, cardiac MRI, and serial measurements of cardiac biomarkers such as high-sensitivity troponins and natriuretic peptides. The analysis revealed that subtle changes in myocardial strain parameters and early biomarker elevations were predictive of subsequent declines in left ventricular function, preceding conventional echocardiographic evidence of cardiotoxicity. Logistic regression analysis highlighted the additive predictive value of integrating biomarker data with advanced imaging findings to identify patients with the highest risk of significant cardiotoxicity. The study concluded that an integrated diagnostic approach, combining detailed imaging assessments with sensitive biomarker analysis, offers a superior strategy for the early detection of chemotherapy-induced cardiotoxicity in breast cancer patients. This proactive diagnostic strategy empowers clinicians to tailor cancer therapy more precisely, balancing oncologic efficacy with cardiovascular safety and underscores the importance of a multidisciplinary approach in the management of patients undergoing potentially cardiotoxic chemotherapy.